Caracterização das infecções relacionadas à assistência à saúde em uma Unidade de Terapia Intensiva - Pereira, Francisco Gilberto Fernandes (2016)
Objective: to analyze Infections Related to Health Care (IRAS) of patients in an Intensive Care Unit. Method: epidemiological retrospective study conducted at the University Hospital of Fortaleza, between 2008 and 2011. Data were collected, organized in tables, and analyzed using descriptive statistics. Results: equal number of female and male patients; average age of 58.3 years; average length of hospitalization and of diagnosis of infection of 21.2 and 11.7 days, respectively; central venous catheter performed in 89.3% of patients; most frequent topography: respiratory in 48.1% of patients; main identified pathogen: pseudomonas aeruginosa in 18.3% of patients; most used antimicrobials: glycopeptides, represented by vancomycin and teicoplanin; and, most frequent clinical outcome: death in 65.4% of patients. Conclusion: IRAS in the intensive care environment affect a large percentage of patients, requiring the implementation of strategies aiming at reducing the statistics and at promoting a safe hospital environment.